MOTIVATION AND WORK DISCIPLINE EFFECT ON THE TEACHERâS PERFORMANCE BY MODERATION HEAD MASTER LEADERSHIP THAT TAKES OBJECTOR PRIMARY SCHOOL TEACHER IN LASEM SUBDISTRICT REMBANG REGENCY - Cuk Dwi Santoso, 12.52.02.0178; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the influence of work motivation and work discipline on the performance of elementary school teachers job satisfaction moderation. Location of the study in the Technical Implementation Unit Office of the District Educational Resources District Apex. In this study population of 124 with a sample of 121 respondents with a purposive sampling method. With a minimum education level criterion D2, minimum age 21 years, minimum term of 4 years, and rank / class minimum gelongan II. Measurements using a Likert scale of 7 (seven) jawaban.Uji alternative instruments used are validity and reliability, while the test model used is the coefficient of determination, F test (Goodness of Fit) and t test (t-test). Hypothesis test used in this study is a regression analysis with the t criteria. Hypothesis testing used the t test at significance level frequency distribution (a) 5%. Â The results showed 12.6% of the change can be explained by the variable performance of work motivation, work discipline and job satisfaction was 87.4% outside of the model is described. The results of the hypothesis test result that (1) motivation have a effect on performance teacher, (2) the discipline of work have not the effect on performance teacher, (3) job satisfaction have not the effect on teacher performance, (4) Principalâs leadership can increase work motivation on tea cherâs performance, (5) principalâs leadership can not decrease work discipline on teacherâs performance. Keywords: Work Motivation, Work Discipline, Kepuasann Work, and Teacher Performance